Different sensitivity of ATP + Mg + Na (I) and Pi + Mg (II) dependent types of ouabain binding to phospholipase A2 - Svoboda, P; Amler, E; Teisinger, J (The Journal of membrane biology, 1988)
The effect of phospholipase A2 and of related agents on ouabain binding and Na, K-ATPase activity were studied in intact and detergent-treated membrane preparations of rat brain cortex and pig kidney medulla. It was found that phospholipase A2 (PLA2) may distinguish or dissociate ouabain binding complexes I (ATP + Mg + Na) and II (Pi + Mg), stimulating the former and inhibiting the latter. Procedures which break the permeability barriers of vesicular membrane preparations, such as repeated freezing-thawing, sonication or hypoosmotic shock failed to mimic the effect of PLA2, indicating that it was not acting primarily by opening the inside-out oriented vesicles. The detergent digitonin exhibited similar effects on ouabain binding in both ATP + Mg + Na and Pi + Mg media. Other detergents were ineffective. The ability of PLA2 to distinguish between ouabain binding type I and II can be manifested even in SDS-treated, purified preparations of Na, K-ATPase. The number of ATP + Mg + Na-dependent sites is unchanged, while the Pi + Mg-dependent sites are decreased in number in a manner similar to that seen in original membranes. This inhibition is completely lost in the reconstituted Na, K-ATPase system, where the ATP- as well as Pi-oriented ouabain sites are inhibited by PLA2.
Keywords: dřeň ledvin; Phospholipases A; Sodium; adenosintrifosfát; fosfolipasa D; hořčík; Phospholipases; Phospholipases A2; fosfor; ouabain; Rats, Inbred Strains; Type C Phospholipases; krysa rodu Rattus; fosfolipasy typu C; zvířata; mozková kůra; sodíko-draslíková ATPasa; Cerebral Cortex; Ouabain; Adenosine Triphosphate; Phosphorus; Kidney Medulla; sodík; fosfolipasy A2; Rats; Sodium-Potassium-Exchanging ATPase; fosfolipasy; Animals; Phospholipase D; Magnesium; fosfolipasy A; inbrední kmeny potkanů